068 Morning Cardiovascular Function in Chronic Cannabis Users and Healthy Controls. (3rd May 2021) - Robinson, LaTroy; Thosar, Saurabh; Stewart, Alicia; Clemons, Noal; Chess, Daniel; Herzig, Maya; Gagnon, Jacqueline; Ordaz-Johnson, Omar; Emens, Jonathan; Shea, Steven; Bowles, Nicole
Abstract: Introduction: In the US cannabis is recreationally legal in 15 states and medically legal in 34 states. Preclinical studies suggest beneficial effects of cannabis on the cardiovascular system (e.g., vasorelaxation). Yet, acute cases of hospitalization after cannabis consumption indicate potential adverse cardiac effects. Vascular endothelial function is a marker of cardiovascular disease and is measured as a change in resting brachial artery diameter (flow-mediated dilation, FMD) during reactive hyperemia. Both resting diameter (positively) and FMD response (negatively) are associated with cardiovascular risk. Resting diameter likely depends on long-term structural changes, and FMD response mostly depends on nitric oxide. Reactive hyperemia is more complex and depends on numerous variables, including adenosine and prostaglandins. FMD is attenuated in the morning when the frequency of adverse cardiovascular events peaks. To begin to understand the effects of chronic cannabis use on the cardiovascular system, in this pilot study, we compared morning measurements of vascular endothelial function, blood pressure, and heart rate between chronic cannabis users and controls while controlling for prior nighttime sleep opportunities. Methods: Participants, cannabis non-users (n=5) and users (n=4), 44% female, age 25.4 ± 3.6 years - no demographic differences between groups, kept a consistent 2-week sleep schedule at home followed by an 8h sleep opportunity at their habitual time in the laboratory. Upon-wakening, we measured resting blood pressure, heart rate, baseline diameter, hyperemic response, and FMD. Statistical differences between groups were calculated using a two-tailed t-test. Results: Systolic and diastolic blood pressures (p=0.13 and 0.26 respectively), heart rate (p=0.97), and FMD response (p=0.99) did not differ between groups. However, chronic cannabis users had a significantly higher baseline brachial artery diameter (mean difference: 1.04 mm ± 0.26, p=0.005), and lower hyperemic response (mean difference: -7944 iu/s ± 2538, p=0.02) compared to non-users. Conclusion: These preliminary findings suggest that chronic cannabis consumption may be associated with adverse structural and functional changes in the vasculature of otherwise healthy young adults. Based on these initial observations, cannabis may act on the cardiovascular system via non-nitric oxide mechanisms. However, it is necessary to increase our sample size to test the robustness of these findings. Support (if any): KL2TR002370, AASM